Circadian lipid synthesis in brown fat maintains murine body temperature during chronic cold - Adlanmerini, Marine (Proc Natl Acad Sci U S A, 2019)
Ambient temperature influences the molecular clock and lipid metabolism, but the impact of chronic cold exposure on circadian lipid metabolism in thermogenic brown adipose tissue (BAT) has not been studied. Here we show that during chronic cold exposure (1 wk at 4 °C), genes controlling de novo lipogenesis (DNL) including Srebp1, the master transcriptional regulator of DNL, acquired high-amplitude circadian rhythms in thermogenic BAT. These conditions activated mechanistic target of rapamycin 1 (mTORC1), an inducer of Srebp1 expression, and engaged circadian transcriptional repressors REV-ERBα and β as rhythmic regulators of Srebp1 in BAT. SREBP was required in BAT for the thermogenic response to norepinephrine, and depletion of SREBP prevented maintenance of body temperature both during circadian cycles as well as during fasting of chronically cold mice. By contrast, deletion of REV-ERBα and β in BAT allowed mice to maintain their body temperature in chronic cold. Thus, the environmental challenge of prolonged noncircadian exposure to cold temperature induces circadian induction of SREBP1 that drives fuel synthesis in BAT and is necessary to maintain circadian body temperature during chronic cold exposure. The requirement for BAT fatty acid synthesis has broad implications for adaptation to cold.